The Amino Acid Transporter JhI-21 Coevolves with Glutamate Receptors, Impacts NMJ Physiology, and Influences Locomotor Activity in Drosophila Larvae - Ziegler, Anna B. (Sci Rep, 2016)
Changes in synaptic physiology underlie neuronal network plasticity and behavioral phenomena, which are adjusted during development. The Drosophila larval glutamatergic neuromuscular junction (NMJ) represents a powerful synaptic model to investigate factors impacting these processes. Amino acids such as glutamate have been shown to regulate Drosophila NMJ physiology by modulating the clustering of postsynaptic glutamate receptors and thereby regulating the strength of signal transmission from the motor neuron to the muscle cell. To identify amino acid transporters impacting glutmatergic signal transmission, we used Evolutionary Rate Covariation (ERC), a recently developed bioinformatic tool. Our screen identified ten proteins co-evolving with NMJ glutamate receptors. We selected one candidate transporter, the SLC7 (Solute Carrier) transporter family member JhI-21 (Juvenile hormone Inducible-21), which is expressed in Drosophila larval motor neurons. We show that JhI-21 suppresses postsynaptic muscle glutamate receptor abundance, and that JhI-21 expression in motor neurons regulates larval crawling behavior in a developmental stage-specific manner.